SHARK - Aqil B. Hamzah (Nanyang Technological University, 2022)
After finding himself incarcerated at the age of 19, a former secret society member finds his calling as a boxer. With the help of his mentor, Muhamad Ridhwan, and the support of his family, 26-year-old Shakur is set on becoming a professional boxer, seeking redemption in the process. This documentary, titled after Shakur’s in-ring moniker, represents his journey of redemption and his personal philosophy. Just like how sharks are unable to swim backwards, Shakur is determined to keep moving forward in life, refusing to let old demons tempt him back into his old lifestyle.